Parautochthonous nappes in the south-eastern Lahn-Dill area, induced by alpine-type nappe thrusting in the Rhenish Massif (Germany) - Flick, Heiner (Palaeobiodiversity and Palaeoenvironments, 2025)
The Lahn-Dill area in the south-east of the Rhenish Massif exhibits sedimentary and volcanic successions of Middle Devonian to early Carboniferous age that were subject to the Variscan orogeny. Included are parts that do not fit either to contemporaneous facies or the structural style of the autochthon and can be attributed to alpine-type nappes of different provenance. The geological development of the Lahn-Dill area is briefly presented and an outline of the nappes is given. In parts of the autochthonous units thick volcanic successions were subjected to low-angle to horizontal thrusting in response to the orogenic deformation as can be observed in two parautochthonous nappes in the east of the Lahn syncline, southern part of the Lahn-Dill area. Of these two, the Hohensolms nappe with early Carboniferous volcanics is more accessible and is described in some detail here.